2021
DOI: 10.1109/tnsre.2021.3104091
|View full text |Cite
|
Sign up to set email alerts
|

Impedance Control of Human Ankle Joint With Electrically Stimulated Antagonistic Muscle Co-Contraction

Abstract: Functional electrical stimulation (FES) is often used,typically in an open-loop manner, to restore paralyzed motor function for daily living activities. Several feedback control strategies have been developed to improve the performance and usability of FES-evoked movement. However, most of them have been position controllers, while the control strategy for human movement has been known as impedance modulation. Moreover, few studies have attempted to use antagonistic co-contraction for FES feedback control desp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Other studies have shown that eccentric contraction may slow the onset of muscle fatigue by increasing muscle torque [ 41 ]. In addition, other studies have also found that the co-contraction of the agonist/antagonist muscle may produce higher loads, and the co-activation of the agonist/antagonist muscle can significantly increase the tension of the Achilles tendon that can further effectively stretch the ankle joint [ 42 , 43 ]. Therefore, the simultaneous stimulation of the agonist/antagonist muscle can improve the joint’s ROM.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that eccentric contraction may slow the onset of muscle fatigue by increasing muscle torque [ 41 ]. In addition, other studies have also found that the co-contraction of the agonist/antagonist muscle may produce higher loads, and the co-activation of the agonist/antagonist muscle can significantly increase the tension of the Achilles tendon that can further effectively stretch the ankle joint [ 42 , 43 ]. Therefore, the simultaneous stimulation of the agonist/antagonist muscle can improve the joint’s ROM.…”
Section: Discussionmentioning
confidence: 99%
“…Compliant control can provide a compromise between control accuracy and safety (Schumacher et al, 2019). Compliant control can control the position and force simultaneously and purposefully, including impedance/admittance control (Kim et al, 2021), hybrid force/ position control (Yang et al, 2020), and parallel force/position control (Wang et al, 2011). Compared to hybrid and parallel force/position control, impedance control focuses more on achieving the target relationship between force and position, but does not necessarily track the expected trajectories (Perez-Ibarra et al, 2019;Chen et al, 2020;Sun et al, 2020).…”
Section: )mentioning
confidence: 99%